2′-Fucosyllactose Ameliorates Inflammatory Bowel Disease by Modulating Gut Microbiota and Promoting MUC2 Expression - Yao, Qianqian; Fan, Linlin; Zheng, Nan; Blecker, Christophe; Delcenserie, Véronique; Li, Huiying; Wang, Jiaqi (Frontiers in Nutrition, 2022)
Gut microbiota dysbiosis, together with goblet cells dysfunction has been observed in ulcerative colitis cases. This study aims to evaluate the potential of 2′-fucosyllactose (2′-FL) supplementation in inhibiting intestinal inflammation through regulating gut microbiota, protecting goblet cells, and stimulating mucin secretion. 2′-FL was orally administered to C57BL/6J mice daily (400 mg/kg bw) for 21 days and 5% dextran sulfate sodium (DSS) was used to induce the colitis in the last 7 days. Meanwhile, fecal microbiota transplantation (FMT) was conducted to test the roles of gut microbiota in the remission of colitis by 2′-FL. Gut microbiota alteration was analyzed through 16S ribosomal RNA (16S rRNA) sequencing. Periodic acid-Schiff (PAS), immunofluorescence staining, as well as mucin 2 (MUC2) and NOD-like receptor family pyrin domain containing 6 (NLRP6) messenger RNA (mRNA) expression in colon fragments was performed and detected. The results showed that the DSS + 2′-FL mice were found to have a slower rate of weight loss, lower disease activity index (DAI) scores, and longer colon lengths than the DSS group (p < 0.05), so in the FMT recipient mice which received fecal microbiota from the DSS + 2′-FL group. In addition, the data revealed that 2′-FL relieved the disorder of DSS-induced gut microbiota, including decreasing the high abundance of mucin-utilizing bacteria in the DSS group, such as Bacteroides, Lachnospiraceae NK4A136, Lachnospiraceae, and Bacteroides vulgatus. PAS and immunofluorescence staining showed that 2′-FL treatment promoted the recovery of goblet cells and enhanced MUC2 and NLRP6 expression, which was also observed in the FM (DSS + 2′-FL) group. Moreover, NLRP6, which has been proved to be a negative regulator for Toll-like receptor 4/myeloid differential protein-8/nuclear factor-kappa B (TLR4/MyD88/NF-κB) pathway, was upregulated by 2′-FL in colon tissue. In conclusion, this study suggests that 2′-FL ameliorates colitis in a gut microbiota-dependent manner. The underlying protective mechanism associates with the recovery of goblet cells number and improves MUC2 secretion through TLR4-related pathway.